Calculadora de interpolación lineal para tablas de mortalidad en Colombia (2024)
The project focuses on developing a computer application that will help users search for and calculate the probability of survival for fractional ages, using as a basis the information provided by the official mortality tables in Colombia. This application will allow users, both professionals in the area of ​​actuarial science and statistics, as well as researchers and decision makers, to make accurate and fast queries, avoiding the need for manual interpolations or complex calculations.